Electron gyroharmonic effects on ionospheric stimulated Brillouin scatter. Issue 16 (21st August 2014) - Mahmoudian, A.; Scales, W. A.; Bernhardt, P. A.; Isham, B.; Kendall, E.; Briczinski, S. J.; Fuentes, N. E. B.; Vega‐Cancel, O.
Abstract Stimulated Brillouin scattering (SBS) and resonant phenomena are well known in the context of laser fusion, fiber optics, and piezoelectric semiconductor plasmas, as well as in various biological applications. Due to recent advances, active space experiments using high‐power high‐frequency (HF) radio waves may now produce stimulated Brillouin scattering (SBS) in the ionospheric plasma. The sensitivity of the narrowband SBS emission lines to pump frequency stepping across electron gyroharmonics is reported here for the first time. Experimental observations show that SBS emission sidebands are suppressed as the HF pump frequency is stepped across the second and third electron gyroharmonics. A correlation of artificially enhanced airglow and SBS emission lines excited at the upper hybrid altitude is observed and studied for second gyroharmonic heating. The SBS behavior near electron gyroharmonics is shown to have important diagnostic applications for multilayered, multi‐ion component plasmas such as the ionosphere.